2009
DOI: 10.1016/j.jacc.2009.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation and Heart Failure in Cardiology Practice: Reciprocal Impact and Combined Management From the Perspective of Atrial Fibrillation

Abstract: The prescription rate of guideline-recommended drug therapy for AF and LVSD-HF is low. Randomized controlled trials targeting this highly prevalent subgroup with AF and HF are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 27 publications
(17 reference statements)
8
68
0
8
Order By: Relevance
“…Moreover, as shown by the Euro Heart Survey on AF, when CHF and AF coexist, the underprescription of guidelines-recommended medical therapy can be further potentiated. 26 Also in our patients, permanent AF was associated with increased mortality. In this regard, Kamath et al 27 demonstrated the importance of an effective biventricular capture to ensure clinical response from CRT in subjects with permanent AF.…”
Section: Discussionsupporting
confidence: 51%
“…Moreover, as shown by the Euro Heart Survey on AF, when CHF and AF coexist, the underprescription of guidelines-recommended medical therapy can be further potentiated. 26 Also in our patients, permanent AF was associated with increased mortality. In this regard, Kamath et al 27 demonstrated the importance of an effective biventricular capture to ensure clinical response from CRT in subjects with permanent AF.…”
Section: Discussionsupporting
confidence: 51%
“…Therefore, careful patient selection should be clinically considered in the application of RDN. The combination of AF and HF is associated with a higher risk of mortality 37. For the management of AF patients with HF, medical therapy including β‐blocker and amiodarone or radiofrequency catheter ablation is clinically considered, although therapeutic strategies for those patients have not been fully established.…”
Section: Discussionmentioning
confidence: 99%
“…Результаты популяционных исследований показывают низкую распространенность длительной антикоагулянтной терапии. В исследовании Euro Heart Survey AF 32% больных не получали анти-коагулянтную терапию, несмотря на отсутствие проти-вопоказаний [20]. В регистре GARFIELD (The Global Anticoagulant Registry in the FIELD) 38% больных с риском развития тромбоэмболических осложнений по шкале CHADS 2 ≥2 не получали антикоагулянты, в то время как 42,5% больных из группы низкого риска (CHADS 2 -0 баллов) проводилась антикоагулянтная терапия [21].…”
Section: Discussionunclassified